Self-efficacy in older adults with depression: a qualitative study - Tri Nurhidayati; Atika Alfia Rizki; Dewi Setyawati; Ah Yusuf; Retno Indarwati (PAGEPress Publications, 2024)
Older people suffering from depression often exhibit low self-efficacy, which causes them to quickly give up on challenges caused by various problems related to ageing, such as physical, social and mental aspects, including depression, which ultimately impact their quality of life and productivity. Depression in the elderly is caused by physical, psychological, and social interactions with other people, especially caregivers in nursing homes. This study employed a phenomenological approach to analyse self-efficacy among older adults suffering from depression through qualitative inquiries. The participants who met the inclusion criteria lived in nursing homes for more than one year and experienced depression. In-depth interviews were conducted using a structured guide with a general self-efficacy scale (GSES), Indonesian version. The study was conducted in an older adult nursing home in 2022 with 14 older adults. The results were divided into four themes - accompanying performance, vicarious learning, verbal encouragement and emotional states - and indicated that older adults with depression experienced poor self-efficacy and described how to cope with poor self-efficacy.